ISLAMIC BOARDING SCHOOL STRATEGY IN IMPROVING QUALITY TADABBUR NATURE BASED STUDENTS - Arifin, Syamsul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research employs a qualitative case study approach to analyze the quality strategy of a pesantren based on tadabbur alam (contemplation of nature) at Nurul Jadid Islamic Boarding School in Paiton, Probolinggo. The study is conducted in Paiton Subdistrict, Probolinggo Regency, East Java. Data collection methods involve observing the teaching activities of instructors using a nature-centric approach, conducting interviews with the instructors, and collecting relevant documents. The data analysis process is carried out in a circular manner, starting from displaying the data to drawing conclusions. The research findings reveal that the tadabbur alam strategy at Nurul Jadid Islamic Boarding School effectively enhances students' cognitive intelligence and has a positive impact on character development, particularly in spiritual, moral, and social aspects. The integration model of tadabbur alam into the pesantren curriculum successfully encompasses various elements of religious, scientific, and environmental education. As an innovation, this research introduces a comprehensive evaluation method, including specific performance indicators. It is anticipated that the outcomes of this study will significantly contribute to the development of quality strategies for pesantren based on tadabbur alam and serve as a reference for other Islamic boarding schools in improving education standards.